Analiza psychokrytyczna poezji Stanisława Barańczaka - Katarzyna Mulet (Przestrzenie Teorii, 2011)
The article is an attempt at a new reading of Stanisław Barańczak’s poetry by using Charles Mauron’s psychocritical method. Four volumes of poems are subjected to analysis, in which the writer’s obsessive metaphors are extracted, allowing the unveiling of his personal myth. It turns out that the romantic hero complex is underlying this myth, that defines the poet’s way of expression of traumatic experiences from his life. Then, the way of recording of such experiences as enslavement by the totalitarian system, alienation in exile, or Parkinson’s disease, is interpreted according to Hanna Segal’s psychoanalytic theory. Barańczak’s writing is gaining then the title of reparation, it becomes a way to recover lost objects from the past by the writer: freedom, stabilization, health, but also the past time, places, events and people.